Emotion regulation and alcohol abuse in second-generation immigrant adolescents: The protective role of cognitive reappraisal. (March 2021) - Laghi, Fiorenzo; Bianchi, Dora; Lonigro, Antonia; Pompili, Sara; Baiocco, Roberto
The individual predictors of drinking behaviors among second-generation immigrant adolescents are still understudied. This study investigated emotion regulation strategies and alcohol abuse in 472 adolescents (86 second-generation immigrants and 386 Italian natives; age range: 17–18). The Emotion Regulation Questionnaire and the Alcohol Use Disorder Identification Test were used to assess cognitive reappraisal, emotional suppression, and alcohol abuse, respectively. Immigrants reported lower alcohol abuse than natives. A negative relationship between cognitive reappraisal and alcohol abuse was found for immigrants, but not for natives. Specifically, cognitive reappraisal was a protective factor against alcohol abuse only for immigrant adolescents. Clinical and research implications are discussed.